2011
DOI: 10.1128/aem.01458-10
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Xylitol Uptake and Metabolism in Gram-Positive and Gram-Negative Bacteria

Abstract: Visible-wavelength Raman spectroscopy was used to investigate the uptake and metabolism of the fivecarbon sugar alcohol xylitol by Gram-positive viridans group streptococcus and the two extensively used strains of Gram-negative Escherichia coli, E. coli C and E. coli K-12. E. coli C, but not E. coli K-12, contains a complete xylitol operon, and the viridans group streptococcus contains an incomplete xylitol operon used to metabolize the xylitol. Raman spectra from xylitol-exposed viridans group streptococcus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
6
23
0
Order By: Relevance
“…The above findings and earlier clinical observations on the caries-limiting role of xylitol receive interesting support from the Raman spectroscopy studies of Palchaudhuri et al (2011), who suggested that uptake of xylitol by Gram-positive and Gram-negative pathogens occurs even in the presence of other high-calorie sugars. Stable integration of xylitol within the bacterial cell wall may discontinue bacterial multiplication.…”
Section: Effect Of Alditols On Oral Bacterial Counts and Dental Plaquesupporting
confidence: 49%
“…The above findings and earlier clinical observations on the caries-limiting role of xylitol receive interesting support from the Raman spectroscopy studies of Palchaudhuri et al (2011), who suggested that uptake of xylitol by Gram-positive and Gram-negative pathogens occurs even in the presence of other high-calorie sugars. Stable integration of xylitol within the bacterial cell wall may discontinue bacterial multiplication.…”
Section: Effect Of Alditols On Oral Bacterial Counts and Dental Plaquesupporting
confidence: 49%
“…[79][80][81][82][83][84] In early work, Choo-Smith et al 85 86 used Raman spectroscopy to quantify filtered waterborne pathogenic microbial contamination, and Pasteris et al 87 used Raman spectroscopy to identify sulfur inclusions in sulfur-oxidizing marine bacteria. Recently, Palchaudhuri et al 88 investigated the uptake and metabolism of the five-carbon sugar alcohol xylitol by gram-positive viridian group Streptococcus and two gram-negative Escherichia coli strains. In assessing Bacillus strains, Hutsebaut et al 89 characterized the influence of culture conditions on the ability of Raman spectroscopy to discriminate between Bacillus cereus, Bac i l l u s p u m i l u s , a n d B a c i l l u s licheniformis.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Our Raman spectroscopic studies have recently confirmed the formation of this xylitol intermediate by the metabolism of xylitol in both Gram-positive and Gram-negative bacteria, provided they contained the xylitol operons [15]. Moreover, we have shown that xylitol exposure interferes with the ability of these bacteria to retain the crystal violet, a dye essential in Gram staining technique [15]. A thinning of bacterial cell wall thickness may have occurred during their growth in xylitol, resulting in this reduced retention of crystal violet molecules.…”
Section: Introductionmentioning
confidence: 53%
“…These pathogens have similar diplococcic morphology and it is known that Streptococcus mitis bacterial species has several similar physiological characteristics common to S. pneumoniae including the ability to partially metabolize xylitol to produce a toxic xylitol intermediate, probably xylitol-5-phosphate [8][9][10][11][12][13][14]. Our Raman spectroscopic studies have recently confirmed the formation of this xylitol intermediate by the metabolism of xylitol in both Gram-positive and Gram-negative bacteria, provided they contained the xylitol operons [15]. Moreover, we have shown that xylitol exposure interferes with the ability of these bacteria to retain the crystal violet, a dye essential in Gram staining technique [15].…”
Section: Introductionmentioning
confidence: 56%